ANALYSIS OF THE COMPOSITE PROPERTIES OF RAMP/LYCAL FIBER VARIATION OF LAYER 1, 2, AND 3 FIBER ON STRUCTURAL MATERIALS OF LSU AIRCRAFT - Wahyuni Fajar Arum; Khairully Nisa Ismulia (Sekolah Tinggi Teknologi Kedirgantaraan, 2022)
Composite material is a combination of two or more materials that produce new properties of the material. This test will be developed for composite reinforcing fibers by using a type of natural fiber that is ramie fiber. This research aims to determine the characteristics of the mechanical properties of the material by density and pressure tests. Density testing aims to determine the value of mass in water, mass in air and density of material. Compressive testing aims to obtain mechanical values, especially the strength and resistance of composite materials to compressive loads. Experiments to be carried out are the manufacture of ramie fiber reinforced composites with 1, 2 and 3 fiber layer variations using the Lycal matrix using the Hand Lay Up method by placing the fiber in a mold and then smearing it with resin. Density testing is performed using a Gravity Meter Balance Densimeter and compressive testing using Universal Testing Mechine (UTM). Based on the results of density testing and compressive testing, ramie fiber composites are lightweight and ductility. In accordance with the nature of the material required on the aircraft that is light and strong, the ramie fiber composite which has lighter properties is a variation of layer 3 fiber with a density value of 0.8504 g/cm3, a composite which has a higher ductility is a variation of layer 2 fiber with strain value 1,849%, and composites which have lower stiffness properties are composites of layer 1 variation with elastic modulus value of 6776.84 MPa. Keywords : Hand Lay Up, Composites, Ramie